Comparing the Effectiveness of Gymnastics Training and Teaching Games for Understaing (TGfU) for Enhancing Creativity and Motivation in Children Aged 4 to 11 - Shakerian , Sepideh; Hosseini Shakib , Kiana; Rezaee , Meysam (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to compare the effectiveness of gymnastics training and the Teaching Games for Understanding (TGfU) model in improving motivation and creativity among children aged 4 to 11 years.  A quasi-experimental design was employed, involving 60 girls aged 4 to 11 years from Mashhad, Iran, who had no prior experience in gymnastics. Participants were randomly assigned to two groups: a gymnastics training group and a TGfU group, each further divided into two age categories (4-7 years and 8-11 years). The interventions were conducted three times a week over eight weeks. Motivation was assessed using the Motivation for Participation in Physical Activities questionnaire, and creativity was evaluated using a coach-assessed Creativity Questionnaire for Children. Data were analyzed using descriptive statistics and one-way multivariate analysis of covariance (MANCOVA) to assess differences between groups. Both interventions significantly improved motivation and creativity, with notable differences in their impacts. The TGfU group exhibited greater improvement in motivation, with a higher post-test mean score (5.63 ± 0.23) compared to the gymnastics group (4.39 ± 0.26). Conversely, the gymnastics training group demonstrated a stronger effect on creativity, with a post-test mean score of 2.30 ± 0.20 compared to 2.35 ± 0.35 in the TGfU group. These findings highlight the distinct strengths of each approach in addressing different developmental domains. TGfU and gymnastics training both offer valuable contributions to physical education, with TGfU excelling in fostering motivation and gymnastics training promoting creativity. Combining these models could optimize their complementary benefits, providing a holistic approach to developing children's physical, cognitive, and emotional skills.